Qing-Luo-Yin Eases T Cells-Mediated Angiogenesis in Adjuvant-Induced Arthritis Rats by Activating PPARγ - Song MK; Wang MQ; Ruan YQ; Cui C; Chen WG; Olatunji OJ; Li Y; Zuo J (Journal of Inflammation Research)
Meng-Ke Song,1,* Meng-Qi Wang,1,* Yu-Qing Ruan,1 Can Cui,1,2 Wen-Gang Chen,3 Opeyemi Joshua Olatunji,4 Yan Li,1,2 Jian Zuo1,3 1Xin’an Medicine Research Center, the First Affiliated Hospital of Wannan Medical College (Yijishan Hospital), Wuhu, 241004, People’s Republic of China; 2Research Center of Integration of Traditional Chinese and Western Medicine, Wannan Medical College, Wuhu, 241003, People’s Republic of China; 3Department of Pharmacy, the second Affiliated Hospital of Wannan Medical College, Wuhu, 241001, People’s Republic of China; 4African Genome Center, Mohammed VI Polytechnic University, Ben Guerir, 43150, Morocco*These authors contributed equally to this workCorrespondence: Yan Li; Jian Zuo, Xin’an Medicine Research Center, the First Affiliated Hospital of Wannan Medical College (Yijishan Hospital), No. 2 West Zheshan Road, Wuhu, Anhui, 241004, People’s Republic of China, Tel +86-13093626158 ; +86-15056477665, Fax +86-553-5739999, Email liyan.0301@163.com; zuojian8178@163.comIntroduction: Qing-Luo-Yin (QLY) is an anti-rheumatic herbal formula potentially activating PPARγ. The study investigated if and how this property contributes to its anti-angiogenesis effects.Methods: Adjuvant-induced arthritis (AIA) rats were orally treated by QLY or rosiglitazone (a PPARγ agonist), and their monocytes and lymphocytes were co-cultured reciprocally in vitro with different sera. Healthy littermates received blood transfusion from QLY-treated or AIA model rats. Two days ahead of sacrifice, a matrigel plug was implanted in the recipients. AIA serum-incubated THP-1 monocytes and Jurkat T cells were treated by a mixture comprised sinomenine, berberine and palmatine. Jurkat T cells-related media and T0070907 were used to stimulate human umbilical vein endothelial cells (HUVECs).Results: QLY and rosiglitazone similarly alleviated joint injuries, synovial angiogenesis and metabolic disorders in AIA rats. Although QLY impaired inflammatory phenotype of AIA rat monocytes in vivo, it cannot be achieved or sustained in vitro. Lymphocytes of QLY-treated AIA rats had a weak inflammatory phenotype and failed to induce inflammatory polarization of monocytes. AIA blood-induced angiogenesis in the matrigel plug, a phenomenon invisible in QLY group. QLY therapy inhibited pathogenic functions of AIA rats’ lymphocytes, shown by changes of cytokines network in the recipients’ joints, where these cells accumulated. The related compounds affected secretion of Jurkat T cells cultured in AIA serum, which lost the potential in activating HUVECs. This effect disappeared in presence of T0070907, a PPARγ inhibitor.Conclusion: Angiogenesis amelioration during QLY therapy is an indirect result from PPARγ activation-caused functional changes of T cells.Keywords: rheumatoid arthritis, Traditional Chinese Medicine, immune, monocyte, vascular endothelial cell, angiogenesis